Polyneuropathy in Acute Lymphoblastic Leukemia Long-Term Survivors: Clinical and Electrophysiological Characteristics With the Impact of Radiotherapy - Slawomir Kroczka; Slawomir Kroczka; Konrad Stepien; Konrad Stepien; Izabela Witek-Motyl; Tomasz Klekawka; Tomasz Klekawka; Eryk Kapusta; Agnieszka Biedron; Agnieszka Biedron; Pawel Skorek; Pawel Skorek; et al. (Frontiers Media S.A., 2021)
Introduction: Acute lymphoblastic leukemia (ALL) is the most common childhood cancer with one of the highest survival rates. Long-term complications that occur after intensive oncological treatment often impair normal daily functioning. However, existing data on peripheral nervous system condition in ALL survivors remain conflicting.Materials and Methods: The study group consisted of 215 ALL survivors. Patients were treated with New York (NY, n = 45), previous modified Berlin-Frankfurt-Münster (pBFM, n = 64), and BFM95 (n = 106) protocols. Time elapsed between the end of the treatment and the control examination varied from 0.3 to 20.9 years. The analyzed patients underwent a neurophysiological analysis with electroneurography (ENG) of motor (median and peroneal) and sensory (median and sural) nerves as well as electromyography (EMG) of tibialis anterior, vastus lateralis, and interosseous I muscles. To estimate the influence of radiotherapy on recorded neurophysiological responses, a joint analysis of NY, and pBFM groups was performed.Results: Clinical symptoms of polyneuropathy were noted among 102 (47.4%) children during the ALL therapy and in 111 (51.6%) during follow-up. At the time of treatment, polyneuropathy was diagnosed in 57.8% participants from NY group, 35.9%-pBFM and 50.0%-BFM95 (p = 0.145). A significantly higher incidence of polyneuropathy was observed during a follow-up in the NY group (68.9%; p < 0.001 vs. pBFM, p = 0.002 vs. BFM95). The most frequent abnormality within all the protocols was demyelination (NY: 44.4%, pBFM: 59.4%, BFM95: 41.5%), in contrast to the least frequently registered isolated axonal changes. The negative influence of oncological treatment on neurophysiological parameters in ALL survivors was observed. Complex disorders of motor nerves, sensory nerves, and motor unit potentials were registered. Motor-sensory neuropathy was the most frequently found pathology in all analyzed protocols. The harmful effect of radiotherapy was also observed in EMG results.Conclusions: Detailed neurophysiological analysis in long-term childhood ALL survivors has shown generalized abnormalities in registered parameters. To our knowledge, the current study is the largest and one of the most comprehensive ones among those examining disturbances in ENG and EMG in this group of patients. Moreover, we are the first ones to demonstrate the negative influence of radiotherapy on peripheral nerve conduction parameters.